Raja ala and Kakulu ala: Two New Improved Varieties of Greater Yam - Thavabalachandran, mangaleswary; De Silva, K P U (JOURNAL OF ROOT CROPS, 2015)
Yams are being cultivated by farmers since ancient times in Sri Lanka. This crop produces high edible energy per hectare, contains more protein than most of the other root and tuber crops and serves as a supplementary food with medicinal properties. Evidence indicated that more than eight edible species of Dioscorea are present in Sri Lanka, of which greater yam (D. alata) and lesser yam (D. esculenta) are widely cultivated. Some of these species, though edible, are not cultivated mainly due to the low productivity and deep penetrating nature of their tubers. However, yams could be popularized, with the identification of high yielding shallow types, which have satisfactory culinary qualities as they need very little attention on agronomic practices. More than 90 accessions of Dioscorea germplasm were collected and maintained at the Horticultural Crops Research and Development Institute (HORDI) fields. Characterization using 25 morphological traits was carried out to identify the species of these accessions. Studies showed that due to the vegetative nature of these crops, the same variety had been known by different names at different locations and different clones had been erroneously called by the same name in different locations and had caused duplications. To avoid duplications, characterization of 25 morphological traits and cataloguing of this collection was done along with the evaluation for their yield potential, quality and other desirable agronomic characters. Thus 30 distinct Dioscorea alata genotypes were identified. Out of these, selections were made and two improved D. alata varieties, Raja ala and Kakulu ala having high yield, good culinary qualities and high marketable value were released in 2007. Key words: Dioscorea alata, Dioscorea esculenta, Characterization